Commuting in dual-earner households: international gender differences with time use surveys - Lucía Echeverría; J. Ignacio Gimenez-Nadal; José Alberto Molina (Review of Economics of the Household, 2024)
Prior studies show men commute longer than women, often due to household responsibilities. However, research on commuting differences within couples is limited. This study examines gender gaps in commuting times and mode choices among dual-earner couples in Spain, Italy, South Korea, and the UK. Using Ordinary Least Squares regressions, we find that the presence of children significantly increases gender gaps in commuting times in Italy and the UK, supporting the household responsibility hypothesis. Conversely, no significant link between children and gender gaps is observed in Spain and Korea. Additionally, children's presence affects commuting mode choices in Italy across all modes, and in Korea for public transit only, with Italian women showing the most changes in commuting mode when children are present.
Keywords: R40; J22; O57; D19; 330; Commuting; Gender differences; Dual-earner couples; Household responsibilities; Multinational Time Use Study